Dinamika Daya Saing Lada Indonesia - Sri Hery Susilowati (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2003)
EnglishIndonesia is one of the major producer contries of pepper (Piper Nigrum L) along with India, Brazil and Malaysia. With the increase of market competition among them in international market, Indonesia has to be able to increase market competitiveness of pepper exports againts competitors. The purpose of this study is to analize the competitiveness of Indonesia pepper exports among the competitors in international market. Time series data of 1985 – 2001 were used and most the data came from the International Pepper Statistic Year Book. The results of analysis showed that for all analysis periodes, Indonesia exports competitiveness has increased to three other competitors, except for the first periode (1985-1996), which India and Malaysia competitiveness is higher than Indonesia. Market distribution effect showed that USA, MEE and Singapore markets are proper market for Indonesia pepper export. IndonesianDiantara negara-negara produsen lada dunia, Indonesia termasuk salah satu produsen utama dunia bersama-sama dengan India, Malaysia dan Brazil. Dengan meningkatnya kompetisi antara negara produsen, Indonesia dituntut untuk mampu mempertahankan daya saingnya di pasar internasional. Kajian ini bertujuan untuk menelaah posisi daya saing ekspor Indonesia relatif terhadap beberapa negara pesaingnya di pasar lada dunia. Data yang digunakan adalah data deret waktu periode 1985-2001 yang bersumber dari International Pepper Community Statistical Year Book. Dari hasil analisis dapat ditunjukkan bahwa untuk seluruh periode analisis, daya saing Indonesia mengalami peningkatan relatif terhadap tiga negara pesaingnya, kecuali pada periode awal (1985-1996) dimana daya saing India dan Malaysia mengungguli Indonesia. Pengaruh distribusi pasar menunjukkan bahwa pasar Amerika Serikat, MEE dan Singapore merupakan pasar tujuan yang tepat bagi ekspor lada Indonesia.